Polyhydroxy Fullerenes Enhance Antibacterial and Electrocatalytic Activity of Silver Nanoparticles - Palomino-Marcelo, Luis (2022)
Silver nanoparticles (AgNPs) are known and widely used for their antibacterial properties. However, the ever-increasing resistance of microorganisms compels the design of novel nanomaterials which are able to surpass their capabilities. Herein, we synthesized silver nanoparticles using, for the first time, polyhydroxy fullerene (PHF) as a reducing and capping agent, through a one-pot synthesis method. The resulting nanoparticles (PHF-AgNPs) were compared to AgNPs that were synthesized using sodium citrate (citrate-AgNPs). They were characterized using high-resolution transmission electron microscopy (HR-TEM), dynamic light scattering, and UV-visible spectroscopy. Our results showed that PHF-AgNPs have a smaller size and a narrower size distribution than citrate-AgNPs, which suggests that PHF may be a better capping agent than citrate. Antibacterial assays using E. coli showed enhanced antimicrobial activity for PHF-AgNPs compared to citrate-AgNPs. The electrocatalytic activity of nanoparticles towards oxygen evolution and reduction reaction (OER and ORR, respectively) was tested through cyclic voltammetry. Both nanoparticles are found to promote OER and ORR, but PHF-AgNPs showed a significant increase in activity with respect to citrate-AgNPs. Thus, our results demonstrate that the properties of forming nanoparticles can be tuned by choosing the appropriate reducing/capping agent. Specifically, this suggests that PHF-AgNPs can find potential applications for both catalytic and biomedical applications